If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -8(2a + 5b) + -1(-4b) = 0 3a + (2a * -8 + 5b * -8) + -1(-4b) = 0 3a + (-16a + -40b) + -1(-4b) = 0 Remove parenthesis around (-4b) 3a + -16a + -40b + -1 * -4b = 0 Multiply -1 * -4 3a + -16a + -40b + 4b = 0 Combine like terms: 3a + -16a = -13a -13a + -40b + 4b = 0 Combine like terms: -40b + 4b = -36b -13a + -36b = 0 Solving -13a + -36b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '36b' to each side of the equation. -13a + -36b + 36b = 0 + 36b Combine like terms: -36b + 36b = 0 -13a + 0 = 0 + 36b -13a = 0 + 36b Remove the zero: -13a = 36b Divide each side by '-13'. a = -2.769230769b Simplifying a = -2.769230769b
| 3x+6+4x-19=43 | | 2X^-4/3X^-3 | | 9x^2-kx+1=0 | | 4a^3+8a^2+5a=0 | | (12f+29)-(5f-11)=-2 | | 18w^8x^9-24w^2x^2y^7= | | 3(p-5)=5(p-5) | | X^2+6x+18=15138 | | 6(-3+3n)=-4(-5n-1) | | 2x^-4/3x^-2y^4 | | 7(a+2)+3=-2(2-5a) | | -6(n+3)-4=-2(n+-3)-4 | | x+1/2x+2/3x=180 | | -2(5v+5)=-6(-5-5v) | | -6(n+3)+-4=-2(n+-3)+-4 | | (11(a-3)+12a)-(6(4(3b-7)-(9b+10))+11)=p | | -3(2-3v+5v)= | | 3x-2=x/2+3 | | 4(5x+3)+x=6(x+2) | | 3x+4+4x-2=90 | | 3x+4-4x-2=3x | | -8(x-4)=-6x-8(x+5) | | -6(n-3)-4=-2(n-3)-4 | | 72+5(y+6)=35-(2x-72) | | 7(2-9v)-6v= | | 3(8x-7)+5x=4(6+8x) | | log(4x+22)-log(2x+1)=1 | | (8(x-2)+9x)-(7(3(2y-5)-(8y+7))+9)=p | | 100-4u/3=5u+6/4+6 | | 5+n+3n=9 | | 2v-34=4(v-9) | | 9/6=p/10 |